2021
DOI: 10.3390/foods10081955
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences and Socioeconomic Factors Decided on Plantain and Plantain-Based Products in the Central Region of Cameroon and Oyo State, Nigeria

Abstract: Plantain is a key staple food in Central and West Africa, but there is limited understanding of its market in Africa. In addition, the cooking methods for enhancing the nutritional value, consumer preference, and willingness to pay for plantain and plantain-based products are not well understood. The knowledge gaps in the market and consumer dimension of the food chain need to be known to increase plantain utilization and guide breeding efforts. This research contributes by examining the cooking methods, consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The basis of consumers' preferences for plantains is complex and goes beyond bunch size, finger size, and finger colour, as consumers may choose specific plantains for a particular meal according to their tribe or socio-cultural eating habits (Newilah et al, 2005). Dury et al (2002) and Udomkun et al (2021) reported that plantain is not considered by consumers as a homogeneous product and their preference for plantain varieties varies with the type of cooking or uses. In addition, the most important factor influencing Cameroonian consumers' choice of plantain and its products is taste (Udomkun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of consumers' preferences for plantains is complex and goes beyond bunch size, finger size, and finger colour, as consumers may choose specific plantains for a particular meal according to their tribe or socio-cultural eating habits (Newilah et al, 2005). Dury et al (2002) and Udomkun et al (2021) reported that plantain is not considered by consumers as a homogeneous product and their preference for plantain varieties varies with the type of cooking or uses. In addition, the most important factor influencing Cameroonian consumers' choice of plantain and its products is taste (Udomkun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dury et al (2002) and Udomkun et al (2021) reported that plantain is not considered by consumers as a homogeneous product and their preference for plantain varieties varies with the type of cooking or uses. In addition, the most important factor influencing Cameroonian consumers' choice of plantain and its products is taste (Udomkun et al, 2021). Therefore, the field performance of a genotype would not guarantee that it will be effectively adopted by producers without sufficient knowledge of the culinary use of the fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified boiled plantain as the most consumed form of plantain in Cameroon. [2][3][4] Varietal improvement has largely been carried out considering agronomic performance and tolerance to pests and diseases, but less attention has been paid to consumers' preferences.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In Cameroon, the most commonly preferred dish is boiled plantain prepared using ripe plantain with a peel more yellow than green. 8 To meet the ever increasing demand for plantain, several research centers, including the Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD) in the French West Indies, the International Institute of Tropical Agriculture (IITA) in Nigeria, Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) in Brazil, the Fundación Hondureña de Investigación Agrícola (FHIA) in Honduras, and the Centre Africain de Recherches sur Bananiers et plantains (CARBAP) in Cameroon, have embarked on plantain varietal improvement. The increased pressures of pests and diseases on plantains and bananas have motivated the development of varieties that are pest and disease tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 A recent study revealed that, in Cameroon, taste was the most important factor affecting choices in consuming fresh plantains and their products. 8 Sanya et al highlighted that better consumption attributes such as taste, texture, and color could increase the likelihood of adopting improved banana hybrids by farmers in Uganda. 18 With these results, it is obvious that sensory evaluation studies of consumer preference are important for demand-driven breeding techniques but they are still difficult to conduct with low-income consumers in Africa.…”
Section: Introductionmentioning
confidence: 99%